Evaluating the Influence of Grey Market Premium on IPO Subscription and Listing Performance - Oraon, Atul (Indian Journal of Research in Capital Markets, 2025)
Purpose : The study aimed to examine three important IPO outcomes––listing price, subscription demand and post-listing stock performance––to examine whether the grey market premium (GMP) served as a good indicator for these outcomes. Design/Methodology : The researcher investigated the relationship between IPO performance and GMP using quantitative methods. Statistical tools such as R2 and p-values are assessed to determine how IPOs could predict GMP subscription levels, listing price, and closing prices. The data were analyzed using regression to assess GMP’s significance in IPO outcomes. Findings : The analysis indicates: • GMP did not serve as a significant predictor for either the listing price (p = 0.560) or closing price (p = 0.558) of IPOs. • GMP showed a small but statistically significant relationship with IPO subscription levels (p = 0.006, R2 = 0.025). • GMP offered limited explanatory power, indicating that factors such as institutional participation, foreign institutional investment, market sentiment, and macroeconomic conditions were likely the primary determinants of IPO performance. Originality/Value : The study added to the IPO literature by closely examining how well the GMP—an informal but commonly used indicator—could predict IPO outcomes. It questioned the belief that GMP is a dependable forecasting tool and instead explained that the GMP mainly reflects investor sentiment. The study also suggested that investors looked at other factors than just GMP. Researchers created models that used multiple variables, and policymakers, to improve transparency in grey market activities to reduce misinformation and speculation.